Fostering Learning in Large Programmes and Portfolios: Emerging Lessons from Climate Change and Sustainable Development - Harvey, Blane; Pasanen, Tiina; Pollard, Alison; Raybould, Julia (Sustainability, 2017)
In ﬁelds like climate and development, where the challenges being addressed can be described as “wicked”, learning is key to successful programming. Useful practical and theoretical work is being undertaken to better understand the role of reﬂexive learning in bringing together different knowledge to address complex problems like climate change. Through a review of practical cases and learning theories commonly used in the areas of resilience, climate change adaptation and environmental management, this article: (i) reviews the theories that have shaped approaches to reﬂexive learning in large, highly-distributed climate change and resilience-building programmes for development; and (ii) conducts a comparative learning review of key challenges and lessons emerging from early efforts to promote and integrate reﬂexive learning processes in programmes of this nature. Using a case study approach, the authors focus on early efforts made in four large, inter-related (or nested) programmes to establish, integrate and sustain learning processes and systems. Eight themes emerged from the review and are considered from the perspective of learning programmes as emergent communities of practice. By investigating how these themes play out in the nested programming, the paper contributes to the limited existing body of evidence on learning in large climate change programmes and identiﬁes areas where future efforts might focus.

Impact evaluation for portfolio programmes on policy influence: Reflections on the Indonesian Poverty Reduction Support Facility - Mackenzie, Jessica; Hearn, Simon (Methods Lab, 2016)
• Donors are increasingly using portfolio-based programmes that embrace ‘good failure’ and adaptive, political programming. • However, measuring the impact of these programmes is challenging, especially for those working on policy influence and building country systems; not only do you need to measure the positive and negative impact of the overall portfolio, but also the different pathways tested. • Programmes, therefore, need a light-touch monitoring and evaluation system that allows it to remain flexible. • Good practice examples of portfolio-based programmes present six strategies to evaluate impact: 1. Develop appropriate logic models 2. Collect observational data throughout implementation 3. Develop stories of change or case studies 4. Understand causal relationships without a counterfactual 5. Purposefully select which activities to study 6. Be explicit about how impact will be valued across the portfolio. • These strategies are only useful if monitoring and evaluation is placed at the centre of programme decision-making.

Multi-project programmes functions, forms and implications for evaluation and learning - Buffardi, Anne; Hearn, Simon (Methods Lab, 2015)
Multi-project programmes can serve different purposes. For instance, they may coordinate multiple implementing entities; standardise management and technical support; compare intervention approaches across different contexts; enhance leverage through joint action; or foster sustainability by building relationships among organisations. • At the same time, multi-project programmes are costly, potentially duplicate other mechanisms that fulfil similar functions, and can dilute focus and create confusion. • To guide decisions on what coordination, evaluation and learning mechanisms are needed, it is helpful to articulate the intended purpose of using a programme model. Identifying the purpose(s) can help staff determine what types of knowledge sharing strategies may be most useful to the programme, and how project and programme theories of change can be sequenced

Summarising portfolio change: results frameworks at organisational level - Simister, Nigel (Intrac, 2016)